Personalized rehabilitation program for older patients with osteoarthritis - V. I. Panikar; E. I. Korshun; S. G. Anikin; O. V. Bochko; E. A. Voronina; M. V. Silyutina; E. S. Kravchenko (Современная ревматология)
Objective: to develop a personalized rehabilitation program for improving age-related resilience (AR), antioxidant status (AOS), the quality of life and reducing pain in elderly patients with osteoarthritis (OA).Patients and methods. The program consisted of two parts. In the first part, we conducted a comparative study to assess the AR (Mahnach test), geriatric status, and AOS (amperometric flow-injection analysis) in 181 subjects in total, with coxarthrosis (n=92) and without it (n=89). The average age of patients in two groups was comparable: 72.1±1.1 and 71.9±1.1 years. Using factor analysis, we developed the personalized rehabilitation program based on the obtained data. The effectiveness of the program was evaluated in the second part of our work. We conducted an additional comparative study of changes in AR, AOS, severity of joint pain (by visual analogue scale, VAS) and quality of life (according to SF-36 questionnaire) in patients with coxarthrosis (n=114).Results and discussion. Patients with coxarthrosis had significantly lower level of AR, total antioxidant, and antiradical activity, and a higher content of Schiff bases as compared to subjects without coxarthrosis (p<0.05). The program of rehabilitation, which included a course of treatment with Chondroquard, significantly improved AR, AOS, quality of life and reduced hip pain compared to the standard OA therapy (p<0.05).Conclusion. The personalized rehabilitation program has a complex positive effect on pain, quality of life, AR and AOS in elderly patients with OA.